Bilateral Traumatic Testicular Dislocation - Nubyhélia Maria Negreiro de Carvalho; Ana Clemilda Ximenes Marques; Ivon Teixeira de Souza; Vanessa Guerreiro Soares; Felipe Gomes do Nascimento; Letícia Macedo Pinto; Luccas Victor Rodrigues Dias; Guilherme Carneiro Teixeira (Case Reports in Urology)
Traumatic testis dislocation is an uncommon condition and usually occurs after direct impact on the scrotum. We present an uncommon case of bilateral testicular dislocation caused by an automotive accident, which is the most frequently associated cause described in literature today. Although the fact that diagnosis can be made either by physical examination or with the use of basic exams such as Doppler ultrasound, it is not uncommon for cases to go undetected and diagnosed late. In this case, there was a late diagnosis, almost one year after the motorcycle accident. Despite this, studies describe preservation of spermatogenesis even after delayed surgical correction. The treatment can be made by manual reduction, but most of the cases need surgical correction. Therefore, it is always necessary to perform the complete physical examination of the polytrauma patient on the first medical exam, in order to avoid the risk of fertility loss, endocrine dysfunction, and future malignancy.